2014
DOI: 10.1161/atvbaha.113.302518
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Two Haplotypes of the Human Endothelial Protein C Receptor Gene

Abstract: Objective-To confirm the effect of the endothelial protein receptor gene (PROCR) haplotypes H1 and H3 on venous thromboembolism (VTE), to study their effect on endothelial protein C receptor (EPCR) expression in human umbilical vein endothelial cells, and to investigate the functionality of H1 tagging single-nucleotide polymorphisms in an in vitro model. Approach and Results-Protein C (PC), activated PC, and soluble EPCR (sEPCR) levels were measured in 702 patients with VTE and 518 healthy individuals. All sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 29 publications
5
37
0
Order By: Relevance
“…There was also a relation between low sEPCR levels and EPCR polymorphism (4678G/C) genotypes, though it was not significant. These results were in agreement with Medina et al who reported that individuals with EPCR polymorphism (4678G/C) have reduced risk for venous thrombosis, elevated plasma activated PC levels and reduced plasma sEPCR levels [19].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There was also a relation between low sEPCR levels and EPCR polymorphism (4678G/C) genotypes, though it was not significant. These results were in agreement with Medina et al who reported that individuals with EPCR polymorphism (4678G/C) have reduced risk for venous thrombosis, elevated plasma activated PC levels and reduced plasma sEPCR levels [19].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Yin et al reported that frequencies of the EPCR gene 6936AG and 6936GG genotypes were higher in patients with venous thromboembolism than in healthy subjects [18]. Moreover, Medina et al reported that those with homozygous mutant EPCR (6936A/G) genotype have an increased risk for venous thrombosis and increased plasma sEPCR levels [19]. Furthermore, the current results presented higher frequencies of the (1651C/G) genotype and lower soluble EPCR levels in cases than in controls.…”
Section: Discussionsupporting
confidence: 66%
“…These observations raised the possibility that PROCR þ /ZEB1 þ cells are naturally present at higher levels in the normal breasts of AA women and that failure to consider natural variation in gene expression pattern, influenced at least partially by genetic ancestry, could have an impact on identifying cancer-induced field effect on the adjacent normal breast. Measuring PROCR itself in the breast tissue is complicated because there are 4 haplotypes of PROCR due to SNPs and only 1 among them is a cell surface protein (20). Because ZEB1 expression is enriched in PROCR þ /EpCAM À cells, we used ZEB1 as a surrogate marker for PROCR þ /EpCAM À cells in unmanipulated breast tissues.…”
Section: Zeb1 þ Cells Are Enriched In the Normal Breasts Of Aa Women mentioning
confidence: 99%
“…It is possible that other genes on chromosome 16q23 and 1q32 influence the PC and PS levels. 16,42,43 PC activity can be modulated also by the genetic variants of EPCR 44 and the polymorphisms of the genes involved in the vitamin K -dependent γ -carboxylation reaction may also influence the activities of PC and PS. 45 It should be also noted that for the measurement of AT activity, both the bovine thrombin-and the FXa inhibition -based tests, together with an antigen method, are advisable to be performed in patients with suspected type II AT deficiency.…”
mentioning
confidence: 99%